The relationship between homestay activities, tourist satisfaction and post-behavioural intentions: a case of Kuala Medang homestay / Muhammad Fadhli Ahmad - Ahmad, Muhammad Fadhli (2013)
Homestay programme in Malaysia is comprised of various ecotourism packages, offering agrotourism, nature-tourism and/or cultural-tourism activities. However, homestay hosts need to improve its activities in order to attract more tourists in the future. There has been a stable decrease in the number of homestay tourist arrivals in Kuala Medang, which is chosen as the setting of this study. A questionnaire was developed to examine tourists’ perception, preference and satisfaction level toward the homestay activities and how it affected post behavioural intentions. A convenient sample of 346 local and international tourists were surveyed and the results showed majority of them were satisfied with the homestay activities which led to positive post behavioural intentions. Activities which tourists most enjoyed were also identified in the findings.